2021
DOI: 10.1007/s11657-021-01005-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between nutrition, energy expenditure and energy availability with bone mass acquisition in dance students: a 3-year longitudinal study

Abstract: Purpose To determine whether risk factors normally associated with low bone mass in athletic populations (i.e. nutrition intake, energy expenditure and energy availability) are significant predictors of bone mass changes in vocational dance students. MethodsThe total of 101 vocational dancers (63 females, 12.8±2.2yrs; 38 males, 12.7±2.2yrs) and 118 age-matched controls (50 females, 13.0±2.1yrs; 68 males, 13.0±1.8yrs) were monitored for three consecutive years. Bone mass parameters were measured annually at imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…We expected that the age of starting ballet training might be a predictor because strenuous ballet training received at an earlier age may have a negative effect on the peak bone mass accumulation and bone mass density ( Amorim et al, 2021 ). A study ( Munoz et al, 2004 ) showed that the menarche delay of young female ballet dancers was positively correlated with years of dance before puberty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expected that the age of starting ballet training might be a predictor because strenuous ballet training received at an earlier age may have a negative effect on the peak bone mass accumulation and bone mass density ( Amorim et al, 2021 ). A study ( Munoz et al, 2004 ) showed that the menarche delay of young female ballet dancers was positively correlated with years of dance before puberty.…”
Section: Discussionmentioning
confidence: 99%
“…So, the effects of age onset may not be as important for lower extremity injury. Previous findings suggested that strenuous training received at an earlier age for young athletes would influence bone development and biomechanical properties of the bone and that might put young athletes at the risk of overuse injuries ( Munoz et al, 2004 ; Amorim et al, 2021 ). Future studies on the association between young ballet dancers or the age starting to dance ballet and injury rate are necessary.…”
Section: Discussionmentioning
confidence: 99%